Neurosensory impairment due to iatrogenesis during endodontic treatment: Literature review (Research, Society and Development, 2023)
Paresthesia related to endodontic treatment is characterized as a disorder that affects nervous tissue, whose origins can be divided into mechanical and chemical injuries. The most affected nerves are the inferior alveolar, lingual and mental nerves and its main symptoms are tingling, burning sensation, numbness and loss of local sensitivity. Among the possible causes, the so-called dental accidents, known as iatrogenic events, can trigger such effects, causing nerve paresthesia. Therefore, this work aims to carry out a literature review to discuss the main iatrogenic factors during endodontic treatment that can cause paresthesia. For the elaboration of the literature review, 22 articles were selected through Google Scholar, PubMed and Lilacs databases with the following terms “endodontics”; "paresthesia" and "nerve", in English and Portuguese indexed in the "Health Sciences Descriptors" (DeCs). The criteria for inclusion of the articles were defined as: articles that discussed the main iatrogenic factors during endodontic treatment that caused paresthesia, published in the last 10 years, and some classic articles, in Portuguese and English. Thus, it is possible to conclude that the iatrogenic factors that cause paresthesia in endodontic treatment include overinstrumentation, excessive extension of the gutta-percha cone, cement leakage, dentinal debris, irrigating solution, mechanical or chemical nerve injury. It is important to have accurate anatomical knowledge and perform the treatment correctly to avoid damage to the periradicular tissues. Thus, the need for elucidation of the probable occurrence of iatrogenesis during endodontic therapy is in good order.